International Competitiveness of the Mediterranean Quartet : A Heterogeneous-Product Approach - Bennett, Herman; Zarnic, Ziga. (Washington, D.C. : International Monetary Fund, 2008)
The real effective exchange rate (REER) is the most commonly used measure for assessing international competitiveness. We develop a methodology to estimate the REER that incorporates two distinctive elements that are not considered in the current literature and apply it to the Mediterranean Quartet (MQ) of Greece, Italy, Portugal, and Spain, whose common pattern of real appreciation has created concern in policy and academic circles. The two elements that we add to the existing literature are (i) product heterogeneity when identifying each country's international competitors and their weights and (ii) a comprehensive treatment of services exports. Our refined measure suggests a modest reduction in the observed REER gap between the MQ countries and the other euro area countries. In particular, considering product heterogeneity and services exports implies a lower real appreciation from 1998 to 2006 on the order of 2-3 percent for all MQ countries. These are difference-in-difference estimates relative to the results obtained for the rest of the euro area countries using the same methodology.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet